ð˜šð˜°ð˜ð˜¢ð˜¯ð˜¶ð˜® ð˜±ð˜¢ð˜ð˜ªð˜¯ð˜¢ð˜¤ð˜¢ð˜¯ð˜µð˜©ð˜¶ð˜® Dun.: aspectos micorrizais - Casagrande, Lilian Isolde Thomazini (REVISTA DE AGRICULTURA, 2020)
ð˜šð˜°ð˜ð˜¢ð˜¯ð˜¶ð˜® ð˜±ð˜¢ð˜ð˜ªð˜¯ð˜¢ð˜¤ð˜¢ð˜¯ð˜µð˜©ð˜¶ð˜® Dun.: aspectos micorrizais